Pendampingan Kesulitan Belajar Matematika Materi Al-Jabar Pada Siswa Siswi SMP Negeri 14 Kerinci Kelas VII - Sari, Novita; Neltiana, Silvia; Yulia, Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The service activity carried out is in the form of mentoring in learning mathematics subjects for class VII C students at SMP Negeri 14 Kerinci. The aim of this mentoring activity is to increase students' understanding, enthusiasm and enthusiasm for learning, especially in mathematics subjects, material regarding arithmetic operations. algebraic form. Class VII C students at SMP Negeri 14 Kerinci have low interest in mathematics lessons, this can be seen from their lack of enthusiasm in studying in class and their low understanding of the material provided. This is known through initial observations and identification carried out in class. This mentoring activity is carried out through teaching and learning assistance to female students using the mentoring method. At the start of this mentoring activity, students interview teachers and students with the aim of finding out the students' abilities before providing mentoring. After being given. mentoring by the service team, the students will be given a final test (posttest) with the aim of finding out the level of success of the mentoring carried out. The results of this activity showed that the response from students was very good and enthusiastic about participating in good study guidance which can increase students' understanding, enthusiasm and enthusiasm in learning algebraic arithmetic operations.